Miszelle - Bojowald, Stefan (Zeitschrift für ägyptische Sprache und Altertumskunde, 2011)
In this article the “Eye-determinativ” after the “ bxn ”-stone is studied once again. The aim is to show, that it could be influenced by the radix “ bAX ” with three different meanings related to the eye.